Trends of Utilization and 90-Day Complication Rates for Computer-Assisted Navigation and Robotic Assistance for Total Knee Arthroplasty in the United States From 2010 to 2018 - Ilya Bendich, MD, MBA (Elsevier, 2021)
Background: Computer-assisted navigation (CAN) and robotic assistance (RA) for total knee arthroplasty (TKA) are gaining in popularity. The purpose of this study is to update the literature on United States technology-assisted TKA trends of national utilization, regional utilization, and 90-day complication rates requiring readmission. Methods: Patients who underwent primary, elective TKA between 2010 and 2018 were retrospectively identified in the PearlDiver All Payer Claims Database (PearlDiver Technologies Inc.). TKAs were classified as conventional, CAN, or RA based on International Classification of Diseases nineth or tenth revision and Current Procedural Technology codes. Annual rates and regional trends of each type of TKA were reported. Ninety-day complications requiring readmission for each group were captured. Multivariable logistic regression was used to identify odds ratios (OR) for all-cause readmission based on TKA modality. Results: Of the 1,307,411 elective TKAs performed from 2010 to 2018, 92.8% were conventional, and 7.7% were technology-assisted (95.2% CAN and 4.9% RA). RA-TKA had the greatest increase in utilization (+2204%). The Western region had the highest utilization of technologies for TKA, while the Midwestern region had the lowest. Ninety-day postoperative complications requiring readmission were highest for conventional TKA and lowest for RA-TKA. RA-TKA (OR 0.68; 97.5% confidence interval 0.56-0.83, P < .001) and CAN-TKA (OR 0.93; 97.5% confidence interval 0.88-0.97, P < .05) had significantly lower odds of all-cause 90-day complications requiring readmission than conventional TKA. Conclusion: Utilization of RA-TKA and CAN-TKA continues to rise across the United States. The use of these technologies is associated with a lower OR of readmission within 90 days postoperatively.